N-Acetyl Cysteine Mitigates the Acute Effects of Cocaine-Induced Toxicity in Astroglia-Like Cells - Badisa, Ramesh B. (PLoS One, 2015)
Cocaine has a short half-life of only about an hour but its effects, predominantly on the central nervous system (CNS), are fairly long-lasting. Of all cells within the CNS, astrocytes may be the first to display cocaine toxicity owing to their relative abundance in the brain. Cocaine entry could trigger several early response changes that adversely affect their survival, and inhibiting these changes could conversely increase their rate of survival. In order to identify these changes and the minimal concentrations of cocaine that can elicit them in vitro, rat C6 astroglia-like cells were treated with cocaine (2–4 mM for 1h) and assayed for alterations in gross cell morphology, cytoplasmic vacuolation, viability, reactive oxygen species (ROS) generation, glutathione (GSH) levels, cell membrane integrity, F-actin cytoskeleton, and histone methylation. We report here that all of the above identified features are significantly altered by cocaine, and may collectively represent the key pathology underlying acute toxicity-mediated death of astroglia-like cells. Pretreatment of the cells with the clinically available antioxidant N-acetyl cysteine (NAC, 5 mM for 30 min) inhibited these changes during subsequent application of cocaine and mitigated cocaine-induced toxicity. Despite repeated cocaine exposure, NAC pretreated cells remained highly viable and post NAC treatment also increased viability of cocaine treated cells to a smaller yet significant level. We show further that this alleviation by NAC is mediated through an increase in GSH levels in the cells. These findings, coupled with the fact that astrocytes maintain neuronal integrity, suggest that compounds which target and mitigate these early toxic changes in astrocytes could have a potentially broad therapeutic role in cocaine-induced CNS damage.